John of Damascus: rewriting the division of heresy and schism - Keith, Zachary M. (Vox Patrum, 2018)
St. John Damascene’s writings on heresies – specifically those texts against Nestorianism and Monophysitism – demonstrate a careful consideration of how thin the line is between schism and heresy. In the texts on heresies, Damascenus endeavors to reread the separation of certain Churches as an ecclesial problem and not only a theological problem. His writings blur the lines between heresy, normally a theological concern, and schism, an ecclesiastical term normally reserved for the separation of Christian Churches. St. John Damascene’s teachings against heresies fit well within the culture of florilegia and compilations. John’s goal, particularly in the De haeresibus, seems to have been to contribute scholarly to the growing world of anti-heretical texts. His texts add to the already large list of known heresies, registering heresies that arose after the council of Chalcedon. Yet John’s texts against heresies are not meant simply to combat false teachings. In some cases, particularly Monophysitism, Damascenus contends that the terms used by orthodox (pro-Chalcedonian) Christians and Monophysite Christians mean the same thing. We must read the Liber de haeresibus in the context of his other writings (e.g. Contra Jacobitas or Contra Nestorianos) in order to determine his true purpose. These definitions aim not to divide Christians based only on teachings, but to show the common understanding present in Christology in spite of different vocabulary. With a proper understanding of heresy, John of Damascus is able to provide a more complete description of the schisms in the Church of his time.